Review paper Current views on the etiopathogenesis of keloids - Bienias, Wojciech; Miękoś-Zydek, Beata; Kaszuba, Andrzej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Keloids are benign mesenchymal tumours, which form post injury as a result of an abnormal wound healing process in genetically susceptible individuals. Clinically they are often confused with hypertrophic scars but in contrast to them, keloids grow beyond the margin of the original wound, invade the surrounding tissue, show no tendency to resolve spontaneously and recur after surgical excision. This kind of disorders occurs only in humans and more often in dark-skinned individuals. The pathogenesis of keloids remains still not completely understood but there are a lot of hypotheses explaining a complicated process of keloids formation: genetic susceptibility, immune function disorder, disturbances in cell proliferation and cell death cycle, altered response to the growth factors and some others. These hypotheses are not alternatives, each one describes another level of the two major processes involved in keloid pathogenesis: hyperproliferation of fibroblasts and excessive production, and deposition of extracellular matrix (ECM) proteins. Further investigations are required for better understanding of the pathogenesis of keloids and should result in more effective treatment of this frustrating clinical problem of wound healing.